DESIGNING OF INTELLIGENT SYSTEM USING FUZZY INFERENCE SYSTEM THE DETERMINATION OF THE GREEN AGROINDUSTRY - Hermawan Prasetya dan Taufik Djatna (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACTRecently, industrial development is directed toward an environmental sound development, called green industry. In implementation of the concept, knowledge of current status of green industry is very important; therefore, development of tools to determine green industry is a necessity. The objective of this research was to design a green agroindustry intelligent system using fuzzy inference system, called SICAH. Development of the system employed twelve variables and 193 rules to determine green industry status of an agroindustry. Moreover, it was implemented simple rules to determine appropriate generic strategy in green industry level enhancement which should be conducted both by government and CEO of agroindustry. Testing the system using dummy data was conducted to ensure fitness of the system in determining of green agroindustry. It was concluded that the system could be implemented for this purpose.Keywords: green industry, intelligent system, fuzzy inference system